Analysis of dendritic cells in tongue, cervical lymph nodes and palatine tonsils of autopsied patients with acquired immunodeficiency syndrome : Análise das células dendríticas na língua, linfonodos cervicais e tonsilas palatinas de pacientes autopsiados com Síndrome da Imunodeficiência Adquirida - Gondak, Rogério de Oliveira, 1978- (2013)
Orientadores: Pablo Agustin Vargas, Luiz Paulo Kowalski